Implementasi Metode K-Means Clustering Untuk Menganalisa Penerima Bantuan Di Desa Palasah - Mar’atun Sholihah, Oliffia; Suarna, Nana; Dwilestari, Gifthera; R, Nining (Jurnal Informatika dan Teknologi Informasi, 2023)
Overcome welfare problems for the community through direct assistance to very poor families in Palasah Village. Related to the problems that have occurred so far, namely that the assistance program targets for poor people, many people who should not have received the assistance, turned out to be inaccurate and valid. So many residents are not registered and recorded accurately. The purpose of this study was to determine the distribution of the accuracy of aid recipients in Palasah Village, Majalengka Regency. The method used in this study is the k-means clustering method, with stages of data collection, training data and data testing that considers several criteria based on: age, economic conditions, housing conditions, and income. With the K-means clustering test k=10, it can produce davies bouldin with sequence k2=0,587, sequence k3=0,529, sequence k4=0,588, sequence k5=0,581, sequence k6=0,529, sequence k7=0,612, sequence k8=0,653, sequence k9 = 0.639, sequence k10 = 0.669, then the conclusion of the Cluster distance performance process produces the best dbi, which is 0.529 in the 3rd order. Can be implemented grouping the data for sewing equipment recipients with the K-Means clustering method, can find out which cluster residents get assistance with sewing tools in Palasah Village. Keywords: Cluster K-Means Algorithm, Social Assistance